2020
DOI: 10.3390/agronomy11010053
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Weed Control in Organic Processing Spinach (Spinacia oleracea L.): Impacts of Cultivar, Seeding Rate, Plant Spacing and Integrated Weed Management Strategy

Abstract: Weed control in organic spinach for the processing market is challenging because of the low tolerance of weed contamination in the harvested produce and the limited physical weeding options. Optimisation of weed control systems is therefore urgently needed. Three field experiments with autumn spinach were carried out in organic fields to evaluate the impact of cultivar choice, seeding rate (300 and 400 seeds m−2), plant spacing management (10.5-cm-wide single rows and 21-cm-wide single or twin rows) and integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 7 publications
4
8
0
Order By: Relevance
“…At the first forage harvest, weed biomass decreased in both FSB 1 and FSB 2 subplots compared to NSB subplots. These results are consistent with those of De Cauwer et al [38], who also indicated that false seedbed is a cultural practice for agroecological weed management that reduces weed biomass at harvest. In another recent study conducted on wheat (Triticum aestivum L.), Shahzad et al [39] found that a false seedbed significantly reduced weed density and biomass compared to conventional seedbed manipulations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…At the first forage harvest, weed biomass decreased in both FSB 1 and FSB 2 subplots compared to NSB subplots. These results are consistent with those of De Cauwer et al [38], who also indicated that false seedbed is a cultural practice for agroecological weed management that reduces weed biomass at harvest. In another recent study conducted on wheat (Triticum aestivum L.), Shahzad et al [39] found that a false seedbed significantly reduced weed density and biomass compared to conventional seedbed manipulations.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, Naeem et al [42] reported that a false seedbed compared to a conventional seedbed preparation resulted in lower weed density and higher yields in barley. Similar results were reported by De Cauwer et al [38] in spinach. In addition, FSB 1 increased forage yield compared to NSB, while FSB 2 further improved forage yield compared to FSB 1.…”
Section: Discussionsupporting
confidence: 92%
“…Similar reports indicated that the use of increased plant populations within the row can improve the competitiveness of even low-competitive crops with slow early growth rates [28,29]. In addition, such practices can be combined with mechanical weed control treatments between crop rows to further suppress weeds [9,[28][29][30]. The study by De Cauwer et al [9] provided evidence on the potential of such practices for weed suppression in spinach in Central Europe.…”
Section: Introductionmentioning
confidence: 88%
“…Weeds are an important obstacle to spinach productivity, as they reduce its commercial biomass and affect the quality of the harvested product [9][10][11]. The impact of weed competition on spinach yield is likely to be higher in fields infested with low-diversity weed communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation